2018
DOI: 10.13075/mp.5893.00695
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction vs. occupational stress – Quantitative analysis of 3 organizational units of a public sector institution

Abstract: The results of the estimation of the polynomial model parameters of ordered categories indicate that the level of perceived stress is related to the level of job satisfaction. The lower the level of stress and stressors in the workplace, the greater the job satisfaction in the surveyed unit. Med Pr 2018;69(3):301-315.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The research results revealed that employees experienced stress at remote work as less severe than at on-site work. This indicates that people staying at home perceived their work as performed under less pressure and risk and more attractive, likable, and calm [ 29 ]. One probable explanation is that individuals who worked from home were not exposed to contact with others, which was deemed risky and a potential threat to getting infected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results revealed that employees experienced stress at remote work as less severe than at on-site work. This indicates that people staying at home perceived their work as performed under less pressure and risk and more attractive, likable, and calm [ 29 ]. One probable explanation is that individuals who worked from home were not exposed to contact with others, which was deemed risky and a potential threat to getting infected.…”
Section: Discussionmentioning
confidence: 99%
“…These resources are crucial in coping with stress, and their absence – manifested by dissatisfaction – can be a source of stress [ 28 ] due to the inability to offset the demands of a work-related situation. Hence, job satisfaction acts as a health-protective factor that undermines the adverse effects of stressors and prevents job burnout [ 29 ]. Therefore, it was included in the present research.…”
Section: Introductionmentioning
confidence: 99%
“…Extant studies evidence that age positively affects job satisfaction (Karsh et al, 2005;Buker & Dolu, 2010;Chou et al, 2011;Lachowski et al, 2018). Employees in the oldest group show the highest job satisfaction, while young employees have minor satisfaction (Rogozinska-Pawelczyk, 2018;DeVaney & Chen, 2003). However, Atefi et al (2015) say that the youth of employees was significantly related to a higher level of job satisfaction.…”
Section: Age and Job Satisfactionmentioning
confidence: 99%
“…Wyniki przeglądu piśmiennictwa ukazują nie do końca spójny obraz omawianego zjawiska. U pracowników zespołów opieki paliatywnej poziom stresu i jego konsekwencji w postaci wypalenia zawodowego nie jest znacząco wyższy niż u przedstawicieli innych dyscyplin medycznych czy grup zawodowych [22,24,28,32,[53][54][55].…”
Section: Wnioskiunclassified